The Expression of Uncoupling Protein 3 Coincides With the Fatty Acid Oxidation Type of Metabolism in Adult Murine Heart - Hilse, Karolina E.; Rupprecht, Anne; Egerbacher, Monika; Bardakji, Sarah; Zimmermann, Lars; Wulczyn, Andrea E. M. Seiler; Pohl, Elena E. (Frontiers in Physiology, 2018)
The involvement of mitochondrial uncoupling proteins 2 and 3 in the pathogenesis of cardiovascular diseases is widely acknowledged. However, contradictory reports show that the functions of UCP2/UCP3 are still disputed. We have previously described that UCP2 is highly abundant in cells that rely on glycolysis, such as stem, cancer and activated immune cells. In contrast, high amounts of UCP3 are present in brown adipose tissue, followed by heart and skeletal muscles - all known to metabolize fatty acids (FA) to a high extent. Using two different models – mouse embryonic stem cell (mESC) differentiation to cardiomyocytes (CM) and murine heart at different developmental stages – we now tested the concept that the expression ratio between UCP2 and UCP3 indicates the metabolism type in CM. Our results revealed the tight correlation between UCP3 abundance, expression of mitochondrial fatty acid oxidation (FAO) markers and presence of multiple connections between mitochondria and lipid droplets. We further demonstrated that the time course of UCP3 expression neither coincided with the onset of the electrical activity in CM, derived from mESC, nor with the expression of respiratory chain proteins, the observation which rendered protein participation in ROS regulation unlikely. The present data imply that UCP3 may facilitate FAO by transporting FAs into mitochondria. In contrast, UCP2 was highly abundant at early stages of heart development and in mESC. Understanding, that the expression patterns of UCP3 and UCP2 in heart during development reflect the type of the cell metabolism is key to the uncovering their different functions. Their expression ratio may be an important diagnostic criterion for the degree of CM differentiation and/or severity of a heart failure.